2007
DOI: 10.1002/pbc.21343
|View full text |Cite
|
Sign up to set email alerts
|

Review of image defined risk factors in localized neuroblastoma patients: Results of the GPOH NB97 trial

Abstract: IDRF were useful in predicting risk and completeness of operation. IDRF failed as independent risk predictors in localized neuroblastoma. INSS more precisely identified patients with poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
61
4
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 6 publications
10
61
4
3
Order By: Relevance
“…The outcome for patients with localised neuroblastoma is favourable with reported OS rates for INSS stage 1 at 98-99% [11], stage 2: 95-99% [7,11] and stage 3: 84% [7]. Similar results were obtained in the present study, with OS in stages 1-3 respectively 99%, 93% and 83%.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The outcome for patients with localised neuroblastoma is favourable with reported OS rates for INSS stage 1 at 98-99% [11], stage 2: 95-99% [7,11] and stage 3: 84% [7]. Similar results were obtained in the present study, with OS in stages 1-3 respectively 99%, 93% and 83%.…”
Section: Discussionsupporting
confidence: 81%
“…We, as others, have confirmed that absence or presence of IDRF is helpful in selecting neuroblastoma patients that may benefit from primary surgery [11,16,17]. The IDRF status of the primary tumour may also be used to assess the risk of surgery in metastatic neuroblastoma [8,18].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Neuroblastoma, the most common extra cranial malignance in children, has established image-defined risk factors during its primary evaluation [46][47][48] and studies showed similar findings of sensibility and specificity on both CT and MR [49]. Early therapy response can be very well evaluated by WB-MRI, possibly even better than I-MIBG [18], but, unfortunately, late therapy evaluation has the same limitation as lymphomas in dealing with scar and residual disease [38 5 Localized STIR images of a lymphoma treatment follow up, there is a good therapy response, different to other total body scan follow up images that can be evaluated by a localized series generated before reconstruction DWI also found significant difference of the ADC map of neuroblastoma compared to ganglioneuroma and ganglioneuroblastoma, adding probably a new utility for this sequence on WB-MRI following further studies [50].…”
Section: Neuroblastoma and Other Small Cell Neoplasmmentioning
confidence: 99%